2021
DOI: 10.1002/emp2.12600
|View full text |Cite
|
Sign up to set email alerts
|

Firework injuries are increasing in the United States: An analysis of the National Emergency Department Sample

Abstract: Background Firework‐related injuries cause significant morbidity to persons in the United States and globally. Prior studies have shown that hands and eyes are frequently injured, with loss of hand function and blindness being common after serious injury. Many jurisdictions in the United States have relaxed laws governing sales of consumer fireworks in recent years. Given the increased availability of consumer fireworks, we sought to determine the incidence of firework‐related injuries compared with historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…There were an estimated 15 600 FRI treated in emergency departments in the USA in 2020 11. Studies using nationally representative data have shown increasing trends in FRI recent time periods 4 11. FRI in Hawaii were like those recorded nationally in a preponderance of male patients, the paediatric age group and type and anatomic location of the FRI.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…There were an estimated 15 600 FRI treated in emergency departments in the USA in 2020 11. Studies using nationally representative data have shown increasing trends in FRI recent time periods 4 11. FRI in Hawaii were like those recorded nationally in a preponderance of male patients, the paediatric age group and type and anatomic location of the FRI.…”
Section: Discussionmentioning
confidence: 64%
“…Although generally used in celebration, fireworks can lead to serious injuries and occasionally death to both users and bystanders, particularly among the paediatric population 1–3. Data from the US National Emergency Department Sample indicated increasing numbers and rates of injuries from fireworks over the 2008 through 2017 period 4. The authors of that study noted the concurrent increasing trend in national consumption of consumer fireworks, which may in turn reflect policy changes in many states, which have facilitated access to consumer fireworks 5.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Consumer Product Safety Commission’s 2020 Fireworks Annual Reports, emergency department (ED)-treated, fireworks-related injuries significantly increased from 2005 to 2020 4. Similarly, using the National Emergency Department Sample, Bitter et al showed an increase in fireworks-related injuries in the USA from 2008 to 2017 5…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al found that blast-related traumatic digit amputations rise significantly in the summer months, implying their relation to the seasonal use of fireworks 9. Bitter et al showed that the burden of firework injuries rested predominately on paediatric and young adult patients, 74.6% of whom were male 5…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Fireworks, an essential part of recreation during various festivals worldwide, can cause potentially grievous ocular morbidity. [3][4][5][6] Ocular injury secondary to fireworks mainly occurs because of a combination of chemical, thermal, and explosive damage to the ocular surface. 3 The carbide gun is one such firecracker capable of causing thermal injury.…”
mentioning
confidence: 99%